Organocatalytic asymmetric synthesis of P-stereogenic molecules - Liu, Junyang; Chen, Hang; Wang, Min; He, Wangjin; Yan, Jia-Lei (Frontiers in Chemistry, 2023)
P-chirality broadly appears in natural and synthetic functional molecules. Catalytic synthesis of organophosphorus compounds bearing P-stereogenic centers is still challenging, due to the lack of efficient catalytic systems. This review summarizes the key achievement in organocatalytic methodologies for the synthesis of P-stereogenic molecules. Different catalytic systems are emphasized for each strategy class (desymmetrization, kinetic resolution, and dynamic kinetic resolution) with examples cited to illustrate the potential applications of the accessed P-stereogenic organophosphorus compounds.